Large red cell-derived membrane particles are major contributors to hypercoagulability in sickle cell disease - Rachel A. Smith (Nature Portfolio, 2021)
Abstract Sickle cell disease (SCD) is one of the most common inherited single gene disorders. Polymerisation of sickle hemoglobin results in erythrocytes that are inflexible and adherent, leading to coagulation, vascular and cellular activation and resultant blood vessel blockage. Previous studies have observed elevated numbers of red cell-derived particles (RCDP), also denoted extracellular vesicles, in SCD plasma. Here, imaging flow cytometry was used to quantify all RCDP in SCD plasma. A more heterogenous population of RCDP was observed than previously reported. Significantly, large right side-out red cell macrovesicles (MaV), 7 µm in diameter, were identified. Most RCDP were right side-out but a minor population of inside-out vesicles was also present. Electron micrographs confirmed the heterogenous nature of the RCDP detected. All MaV are decorated with prothrombotic phosphatidylserine (PS) and their removal from plasma lengthened clotting times by more than three-fold. Removal of all right side-out RCDP from SCD patient plasma samples resulted in a seven-fold increase in clotting time. These results indicate that MaV comprise a large area of prothrombotic membrane and are thus major contributors to hypercoagulation in SCD. Consequently, controlled removal of MaV and PS exposed RCDP from plasma could provide a novel therapy for managing this disease.